Ação do dimetil-sulfóxido na isquemia de retalhos randômicos de pele em ratos - Almeida, Kleder Gomes de [UNIFESP] (2004)
Purpose: To evaluate through the morphologic study (macro and microscopic) the effectiveness of DMSO in the genesis of the distal necrosis of random skin flaps in rats. Methods: 30 male rats were used, lineage Wistar, weight between 220 and 363g and 3 months medium age .The skin flap (8x2cm) with remained cranial vessels it was unstuck, restored at his bed and sutured with polyamide 4.0. The control-group CT (n=10) don t received any medication, the simulated group -SM (n=10) it received the volume of 1mL of subcutaneous saline solution, divided in ten applications along the skin flap, the experiment group (n=10) it received the injection of 1ml of DMSO5%. After seven days they were appraised the areas of distal necrosis and picked material for the histology study. Results: The measures of the necrosis areas (CT=47.99, SM=58.78, EX=41.57) and the percentages of the necrosis areas (CT=29.98, SM=36.73, EX =23.99) they were shown smaller in the EX group (p < 0,05). The qualitative histology study showed, in the group EX, larger angiogenic presence, smaller destruction of the enclosures and of the conjunctive stroma and presence of fibroblasts in more precocious period than in the two other groups. Conclusion: The analysis of the collected data can infer that DMSO had beneficial action on the random skin flaps, expressed by the smallest area of distal necrosis and for the histology aspect of repairing tissue more precocious.